Les exposants morphologiąues et syntaxiques de la symétrie en français - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2003)
The present paper deals with the exponents of symmetry in contemporary French. Apart from expressions that do not bear any markers of this type of relation, there are others where this property is closely related to their morphemic structure. It is argued that such a morphological exponence holds when verbal stems are preceded by the prefixes entre- and co-. The forms with these markers are carefully scrutinized with regard to their combinatory and derivational features. It is claimed that the verbs with the entre- prefix are, as far as the word-formation is concerned, more regular than those with co-. If the morphemic analysis fails in explaining the semantic value of an affix, it is necessary to fall back on the description of syntagmatic properties of lexical items that incorporate it. Of special importance among syntactic exponents of symmetry is the adjunction of prepositional phrase introduced by avec. This operation establishes unequivocally the semantic value of verbs with co-. Furthermore, if such a prepositional phrase is attached to one-place predicates, it adds a new argument and becomes, jointly with the verb, the exponent of a symmetric relation. The last syntactic exponent of symmetry dealt with here is the expression l’un l'autre. Once it is added to the verb phrase, it emphasizes the presence of such a relation in the meaning of the predicate. The paper attempts to cast a new light on the way syntactic structures of the phrases with predicative expressions that designate symmetric relations are modified.